Emerging research themes in ferroptosis research for non-small cell lung cancer: a bibliometric and visualized analysis - Zhang, Wenbo; Gu, Jianwei; Chen, Yong; Jiang, Guolu; Gonzalez-Rivas, Diego; Ma, Minjie; Chen, Chang (Frontiers in Immunology, 2025)
BackgroundFerroptosis, an iron-dependent form of regulated cell death, has garnered significant attention as a potential therapeutic target in oncology due to its unique mechanism involving lipid peroxidation and reactive oxygen species accumulation. In non-small cell lung cancer (NSCLC), ferroptosis offers promising strategies to overcome drug resistance and enhance the efficacy of existing therapies. While the literature on ferroptosis in NSCLC has expanded rapidly over the past decade, a comprehensive understanding of its research trends, global collaboration patterns, and emerging hotspots remains lacking.ObjectiveThis study employs bibliometric and visualized analysis to systematically evaluate global research trends, influential contributors, and thematic evolution in ferroptosis research for NSCLC. The findings aim to guide future investigations and promote interdisciplinary collaborations.MethodsData were extracted from the Web of Science Core Collection on December 24, 2024. Bibliometric tools including VOSviewer, CiteSpace, and GraphPad Prism were used to analyze publication trends, citation patterns, collaborative networks, and research hotspots. Key indicators such as publication output, geographic contributions, institutional performance, and keyword co-occurrence were visualized to elucidate the field’s development.ResultsA total of 964 publications from 52 countries and regions were analyzed, with China and the United States emerging as the most influential contributors. Chinese institutions such as Fudan University and Central South University led in publication output, while US-based authors had the highest citation impact. Research hotspots included ferroptosis mechanisms, biomarkers, oxidative stress, immunotherapy, and drug resistance. Keyword and citation analyses reveal an increasing emphasis on integrating ferroptosis inducers with immune checkpoint inhibitors and leveraging nanomedicine for targeted therapy.ConclusionThis bibliometric analysis highlights the rapid expansion of ferroptosis research in NSCLC, revealing key contributors, global trends, and emerging areas of focus. The integration of ferroptosis with immunotherapy and precision medicine holds immense promise for advancing NSCLC treatment. Future research should prioritize international collaboration, explore resistance mechanisms, and harness advanced technologies such as nanomedicine and artificial intelligence to maximize therapeutic potential.